Participatory Governance in the EU - Lindgren, K. author. aut Link
IX, 162 p.
Keywords: An empirical assessment of whether participatory governance reforms within the EU enhance or endanger democracy. Many consider allowing civil society to take an active role in EU policy-making to offer the most effective means of enhancing democracy in the EU, whereas others argue that such attempts deepen the EU's democratic deficit.